Business of Share Trading : From Starting Out to Cashing in with Trading. - Wilson, Leon (John Wiley & Sons, 2012)
Successful trader and best-selling author Leon Wilson knows how to make a living trading on the sharemarket. He also knows that because trading requires discipline, time and self-education, 90 per cent of those who attempt it will fail within two years. In concise and clear language, The Business of Share Trading, second edition, shows how you can take control and profit from an active sharemarket portfolio. From developing a plan and financing your capital investment, to setting up a home office and keeping accurate records, this newly expanded edition offers step-by-step guidance to all aspec.